Individual and Society; Controversy Over the Views of Contemporary Muslim Philosophers - Yahya Bouzarinejad; Keivan Soleimani; Elaheh Talebzadeh (آموزه‌‌های فلسفه اسلامي)
Society and the individual and the relationship between the two is one of the most important philosophical issues for thinkers. Modern social scientists (companions) have offered three perspectives in answer to this question. Some have given principality to the individual in relation to society, some have considered society to be principal in relation to the individual, and others have taken a combined view between the individual and society. The importance of this issue is that any answer to the question of the relation and principality of the individual or society, forms the path of humanities and social sciences research. The question of this research is what is the response of contemporary Muslim philosophers to the relationship between the individual and society based on rational and philosophical principles, although in the works of early Muslim thinkers such as Fārābī, Khajeh Naṣir al-Din al-Ṭūsī and Ibn Khaldūn, one can find an answer to the relationship between the individual and society. However, due to the familiarity of contemporary Muslim philosophers with modern social sciences, different and independent works and opinions have been expressed and written about the relationship between the individual and society or the principality of the individual or society. The author believes that contemporary Iranian philosophers, in terms of their response to the relationship between the individual and society, can be classified into three groups: the principality of the individual, the principality of society and the principality of society and the individual. In order to prove their point of view, each of them has mentioned rational and scriptural (traditional) proofs that have caused the conflict of opinions and the emergence of innovative theories based on Islamic teachings. In this research, by referring to the available sources and works and describing, documenting and analyzing the content, the conflicts and discussions formed about the individual and society have been dealt with.